English Fun: Meningkatkan Minat Belajar Bahasa Inggris Anak - Abdul Gapur; Nurhayati Nurhayati; Silva Fadilah Suparman (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Children in rural communities have few opportunities to interact in fun ways to learn English. This means low motivation and little exposure to the language as it is really used. Learning opportunities that foster language development and learner confidence might be available thru community-based education programs. This community service was conducted at the Banyuwangi Community Learning Center, Cibitung District, Sukabumi Regency. This community service is aimed to improve the English skill of young students thru English Fun program. The program was conducted for a month (Monday-Thursday) with elementary and secondary school students. The activities were participatory and learner-centered thru interactive games, songs, storytelling, vocabulary enrichment, simple conversations, role-playing and collaborative learning. The activities were intended to create a happy learning environment, to promote active participation, and to facilitate meaningful communication in the English language. Implementation showed increased student enthusiasm, confidence, classroom participation and willingness to use English in daily interactions. The constant practice helped the learners to improve their basic vocabulary acquisition, pronunciation and communication skills. To conclude, the English Fun program was effective in improving the basic English skills of children and cultivating positive attitudes toward learning English. With this program, we highlight the positive effects of sustainable community-based learning projects that help increase access to education and support English language learning for rural community children.